(untitled) (Modern American Journal of Medical and Health Sciences, 2025)
Cells maintain their structure and function through continuous energy exchange with their surroundings. These processes are governed by the fundamental laws of thermodynamics , which ensure that energy is conserved while entropy tends to increase. In cancer cells , these principles become especially important , as changes in metabolism support uncontrolled proliferation and disrupt energy balance (Haynie , 2014). ATP plays a central role in this system , providing free energy for endergonic reactions through coupling mechanisms. However , in malignant cells , ATP production and consumption pathways are reprogrammed — a phenomenon known as the Warburg effect. This shift results in altered Gibbs free energy (ΔG) , increased heat production , and changes in cellular heat capacity , all reflecting the thermodynamic imbalance within the cell. Understanding these processes through thermodynamic analysis allows us to connect molecular energy transformations to large-scale biological behavior , revealing how cancer cells sustain their growth far from equilibrium conditions.